Cost-effectiveness analysis of sintilimab plus pemetrexed and platinum versus chemotherapy alone as first-line treatment in metastatic non-squamous non-small cell lung cancer in China - Huiqin Liu; Ying Wang; Qi He (Health Economics Review, 2022)
Objective: In frst-line treatment of advanced or metastatic nonsquamous non-small-cell lung cancer (NSCLC), the ORIENT-11 study demonstrated a signifcant progression-free survival and overall survival for sintilimab plus chemotherapy in comparison with chemotherapy alone. But the cost-effectiveness of the two treatment schemes is unclear in China. The objective of the current study was to evaluate the cost efectiveness of sintilimab plus chemotherapy versus Platinum-based chemotherapy for locally advanced or metastatic squamous NSCLC in China. Methods: We performed an economic evaluation from the perspective of the Chinese healthcare system using a partitioned survival model with three mutually exclusive health states: progression free, post-progression, and death. The circulation cycle of the model was 3 weeks and the study time limit was 10 years. Efficacy data were obtained from the ORIENT-11 clinical trial. Cost and utility values were derived from published studies and online price databases. The primary outcomes of the model were quality-adjusted life-years (QALYs), costs, and incremental cost-effectiveness ratios (ICERs). One-way sensitivity analysis and probability sensitivity analysis were used to verify the robustness of the base-case analysis results. Results: Sintilimab plus chemotherapy provided an additional 0.6 QALYs. The total cost per patient was CNY413,273.16 for sintilimab plus chemotherapy and CNY280,695.23 for Platinum-based chemotherapy. The ICER for sintilimab plus chemotherapy was CNY220,963.22/QALY. Sensitivity analyses found the results to be most sensitive to the cost of pemetrexed and utilities of PF state. In the probabilistic sensitivity analysis, sintilimab was cost-efective in 78.6% of the simulations, assuming a willingness-to-pay threshold (WTP) of CNY242,928 per QALY. Conclusion: Compared with chemotherapy alone, the sintilimab plus chemotherapy is likely to be a cost-effective option as the first-line treatment for locally advanced or metastatic nonsquamous NSCLC in China.
Keywords: 330; Non-small cell lung cancer; Sintilimab; Cost-efectiveness analysis; Partitioned survival model